Chronic inflammation, insulin resistance, psoriasis - which have in common? - M. S. Rasin (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
Psoriasis is recognized as system immune inflammatory disease at a certain genetic basis. It was found that psoriasis develops under the influence of chronic systemic inflammation low intensity (low grade inflammation) that induced insulin resistance, and is one of the clinical forms of the Immune Metabolic Disease (IMD), along with atherosclerosis, hypertension, type 2 diabetes, obesity and many other diseases, whose tight relationship with psoriasis are installed. Knowledge of the etiology, pathogenesis and molecular mechanisms of communication with other clinical forms of the IMD opens up new ways of prevention and treatment of psoriasis. Please note that other diseases associated with psoriasis, occurring hidden, often have greater predictive value for the life and health of the patient than mild or moderate forms of psoriasis, and be not limited to ascertaining the diagnosis and symptomatic treatment and actively participate in prevention. Debated question of the application of funds, suppressing systemic inflammation and insulin resistance in the treatment of psoriasis.